POSSIBILITIES AND MODERN TRENDS OF INFORMATION TECHNOLOGIES IN MEDICINE (The New Uzbekistan Journal of Medicine, 2025)
Today, the development of the healthcare system is unimaginable without information technologies. This article discusses the areas of application of information technologies in medicine, their role in creating convenience for patients, their function in facilitating the work of doctors, and their impact on the global healthcare system. It also analyzes the advantages of telemedicine, artificial intelligence, electronic healthcare systems, and mobile medical applications, as well as the problems encountered in their use.